Effect of Selected Humectants as Water Activity Modifiers on the Quality of Model Khoa System - Badola, Richa; Panjagari, Narender Raju; RRB, Singh; Singh, Ashish Kumar; Shaik, Abdul Hussain (Indian Journal of Dairy Science, 2017)
Water activity and other physical properties including moisture content and instrumental colour parameters, as well as sensory parameters were analyzed to investigate the effect of addition of humectants on model khoa system. Model khoa system was specially designed to get consistent and fast results, for selection of humectant as a hurdle for preservation of khoa based products such as khoa, burfi, peda, etc. instead of undergoing laborious manufacturing processes involved in khoa and khoa based indigenous dairy products. All the five humectants studied such as polydextrose, maltodextrin, mannitol, sorbitol and corn syrup were found to have a significant (P